Legal Framework on Land Administration in Nigeria - Alkali, Muhammad Bashir (ABUAD Law Journal, 2022)
Land Administration in Nigeria dates back to pre-colonialism Nigeria. Before the advent of colonialism, customary land laws applies in different parts of the country especially southern Nigeria while Islamic law applies in most parts of Northern Nigeria. After the advent of colonialism, several ordinances and proclamations were passed by the colonial administration on land administration. This paper aims to identify key laws and stakeholders in land administration with intent to suggest improvement on land administration in Nigeria. Several laws govern land administration in post independence Nigeria. The Land Use Act 1978 is one of the extent laws on land administration in Nigeria. The court, the Bar and the Executive are key stakeholders in land administration in Nigeria. Use of modern technology, training of staff and staff welfare are some important suggestions for better land administration in Nigeria. Doctrinal methodology was adopted in this paper due to its nature and objectives.